Legal Measures Concerning Technology Transfer for Industrial Development - Chimsuntorn, Vinita (Huachiew Chalermprakiet Law Journal, 2024)
Thailand adopts economic liberalization in hopes of receiving technology through foreign investment and technology transactions. Nevertheless, Thai personnel do not sufficiently benefit from technology transfer, comparing to the benefits that foreigners reap from Thailand’s resources. Furthermore, Thailand still lacks a concrete regulatory framework for technology transfer. China, Japan and Vietnam are under binding commitments as World Trade Organization’s members, but these three countries can set clear regulatory frameworks for technology transfer. Since China and Japan put the antimonopoly rules in the field of intellectual property into effect, which prevent the abuse of intellectual property rights, and lead to the balance of intellectual property protection and fair technology transfer. While Vietnam collects and systematically organizes the regulations concerning technology transfer into a single law. The researcher proposes that the antimonopoly rules in the field of intellectual property and regulations concerning technology transfer should be codified into a model law, in a manner consistent with World Trade Organization’s regulations. This clear regulatory framework will eventually result in the fair transfer of technology and industrial development.